Research and construction of new digital foundation for the fusion between IPv6 and 5G - LIN Chujian; JIAO Baochen; LIANG Zhelong; ZHU Yue; ZHAO Xing; LI Tao (Tongxin xuebao)
Based on the current situation of the campus network of Nankai University, new generation information network technologies such as IPv6 and 5G were studied, a new basic network integrating Wi-Fi campus network and 5G private network based on IPv6 protocol, IPv6 adaptation and application pilot deployment of the information innovation platform was built, a new digital foundation integrating IPv6 and 5G for plug and play against IPv6 was carried out and constructed, a mature cloud network fusion solution for the deployment of smart campus business system and a new basic network environment and trusted computing resources for the training, technology research and innovation of professionals in the next generation Internet related disciplines were provided, and the digital transformation of university education was enabled.